Nowe ujęcie neutralności światopoglądowej i prawa do wolności religii w orzecznictwie belgijskim ostatnich lat elementem przemian w relacjach państwo – Kościół w Królestwie Belgii - Falski, Jacek (PRAWO i WIĘŹ, 2025)
This paper focuses on the changes currently taking place in Belgium regarding the right to freedom of thought, conscience and religion (freedom of religion). This is an important issue, as Belgian courts have recently issued several interesting judgements in this area that clarify the relevant constitutional regulations. A key issue in this context is the complex nature of the concept of neutrality as it is applied in Belgium. The author seeks to outline and explain it to the reader.